PENGEMBANGAN E-LKPD BERBASIS WIZER.ME PADA MATA PELAJARAN IPAS MATERI BAGAIMANA KITA HIDUP DAN BERTUMBUH KELAS V SD - Lia Syafitri; Dara Fitrah Dwi; Hasanah; Nurmairina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to: 1) determine the validity of the application of learning to E-LKPD based on wizer.me . 2) determine the practicality of the application of learning to E-LKPD based on wizer.me . 3) determine the response of students through E-LKPD based on wizer.me grade V on the material how we live and grow. This study is a type of research and development with reference to the ADDIE model which has 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation . The instrument used to collect data is a questionnaire. The results of the validation of E-LKPD media experts, the overall assessment of the media expert validation obtained a percentage of 82% of 10 statements. The results of the validation of the material expert assessment obtained a percentage of 90% of 10 statements. The results of the validation of the teacher's practicality obtained a percentage of 96% of 10 statements. The results of the validation of the student response assessment obtained a percentage of 85% of 10 statements. Therefore, it can be concluded that the E-LKPD based on wizer.me on the subject of Natural Sciences, material on How We Live and Grow, grade V of Elementary School, is valid and practical to use.